Marijuana use impacted by legalization and individual factors - Parnes, Jamie E., author; Conner, Bradley T., advisor; Chavez, Ernest, committee member; Coatsworth, Doug, committee member (Colorado State University. Libraries, 2016)
In 2014, marijuana became legal for recreational use for adults 21 and older in Colorado (Colorado Const. art XVIII § 16., 2012). There are potential health risks related to marijuana dependence, which are more prominent in adolescent users (Volkow, Baler, Compton, & Weiss, 2014). Medical marijuana legalization has not been shown to increase marijuana use or prevalence of dependence (Cerdá, Wall, Keyes, Galea, & Hasin, 2012). Changes related to legalization may include increased availability and social acceptance, as well as decreased price and perceived harm of use (Hopfer, 2014). There also may be increased interest in moving to Colorado related to the changes in marijuana laws (United States Census Bureau, 2015; Institutional Research & Analysis, 2014). The facets of sensation seeking, risk seeking and experience seeking, influence marijuana use (Zuckerman, 2007; Conner & Henson, 2011). Sexual orientation has a quadratic relation to marijuana use (Ford & Jasinski, 2006). Use among bisexuals is higher than use at either end of the spectrum (Eisenberg & Wechsler, 2003). Based on these findings, several hypotheses were made. First, marijuana use would increase in college students after legalization, however just for those 21 and older. Next, risk seeking and experience seeking would both uniquely moderate marijuana use before and after legalization and in underage and of-age students. Third, sexual orientation would have a quadratic relation with marijuana use. Finally, the relation between the influence of marijuana leglislation on non-residents decisions to attend a Colorado college and marijuana use was examined. Data was collected from undergraduate students (N = 5241) at a Colorado university. Participants were assessed for marijuana use behavior, sensation seeking, sexual orientation, and influence of marijuana laws on non-resident decision to attend Colorado schools. Pearson’s Chi-square, analysis of variance, negative binomial regressions, and polyserial correlations were used to test the hypotheses. Results indicated that marijuana use has increased since legalization for all students, but moreso for those over 21 (p < .001). No differences in frequency of past month use was found between pre and post legalization (p = .615). Regression analysis found experience seeking to be a significant predictor of past 30 day use (p <.05). Additionally, risk seeking predicted use for those under 21 (p <.01). A quadratic relation was found between sexual orientation and past month use, where use increased at a decreasing rate from the homosexual end of the spectrum to the heterosexual end (p <.01). Correlations were found between degree of marijuana law influence and both past 30 and lifetime use among non-resident college students (ρ = 0.29, p < .001; ρ = 0.17, p < .001). Overall, legalization, experience seeking, underage risk seeking, sexual orientation, and legislation influence on decision making all predicted marijuana use. These findings may help inform other states considering legalization of potential outcomes and groups at higher risk of marijuana use. Future research should examine longer term effects of legalization, as well as effective interventions.